Effect of blended learning on student performance in K‐12 settings: A meta‐analysis - Li, Shuqin; Wang, Weihua (Journal of computer assisted learning, 2022)
Background Blended learning programs in Kindergarten through Grade 12 (K‐12) classrooms are growing in popularity; however, previous studies assessing their effects have yielded inconsistent results. Further, their effects have not been completely quantitatively synthesized and evaluated. Objectives The purpose of this study is to synthesize the overall effects of blended learning on K‐12 student performance, distinguish the most effective domains of learning outcomes, and examine the moderators of the overall effects. Methods For the purpose, this study conducted a meta‐analysis of 84 studies published between 2000 and 2020, and involved 30,377 K‐12 students. Results and Conclusions Results revealed that blended learning can significantly improve K‐12 students' overall performance [g = 0.65, p < 0.001, 95% CI = (0.54–0.77)], particularly in the cognitive domain [g = 0.74, p < 0.001, 95% CI = (0.61–0.88)). The testing of moderators indicates that the factors moderating the impact of blended learning on student performance in these studies included group activities, educational level, subject, knowledge type, instructor, sample size, intervention duration and region. Implications The results indicate that blended learning is an effective way to improve K‐12 students' performance compared to traditional face‐to‐face (F2F) learning. Additionally, these findings highlight valuable recommendations for future research and practices related to effective blended learning approaches in K‐12 settings. Lay Description What is already known about this topic Blended learning is gaining increased popularity in Kindergarten through Grade 12 (K‐12) settings. Studies have resulted in inconsistent conclusions on the effect of blended learning in K‐12 settings. More rigorous, evidence‐based studies on blended learning are needed in K‐12 settings. What this paper adds Reports the first meta‐analysis on the effects of blended learning on K‐12 student performance compared to traditional face‐to‐face learning. Blended learning significantly improves K‐12 students’ overall performance (g = 0.65), particularly in the cognitive domain (g = 0.74). The effect of blended learning is impacted by the group activities, educational level, subject, knowledge type, instructor, sample size, intervention duration and region. Implications for practice and/or policy Blended learning is an effective instructional strategy in K‐12 settings. Adding group activities can significantly enhance the overall effect of blended learning. Blended learning developers should develop appropriate blended learning courses for different educational levels, subjects and knowledge types.